A new species of Rubus L. (Rosaceae) from Arunachal Pradesh, India - Dash, Sudhansu Sekhar; Gupta, Chandani; Bhuyan, Lakhi Ram (Phytotaxa, 2016)
A new species, Rubus haridasanii, from Arunachal Pradesh, Eastern Himalaya, is described and illustrated. It is closely related to Rubus preptanthus but differs by the presence of caudate-acuminate leaves, 5–6-flowered inflorescences, stipitate glandular pedicels and calyx, delicate needle-like prickles on the calyx, caudate apex of the sepals. The distinct foliar as well as floral morphology of R. haridasanii differ from all previously described species of Rubus. Differences in key morphological characters of R. haridasanii and R. preptanthus are also tabulated. In addition, pollen morphology is described based on light (LM) and scanning electron microscopy (SEM).